Simplifying the Choice of Forum: A Response to Professor Clermont and Professor Eisenberg - David E. Steinberg (Washington University Law Quarterly, 1997)
Every now and again, an article appears that provides new insights into a familiar topic. The recent Cornell Law Review article by Professor Kevin M. Clermont and Professor Theodore Eisenberg, Exorcising the Evil of Forum-Shopping, is such a rare article. In defending current transfer practice under section 1404(a) of the Federal Judiciary Code, Professor Clermont and Professor Eisenberg present a wealth of empirical data. Their findings provide valuable information not only about transfer practice in federal civil cases, but also about forum selection in the federal courts. Professor Clermont and Professor Eisenberg have written a clear and original article. And I disagree with almost all of their conclusions. I disagree with Professor Clermont and Professor Eisenberg on the following points. First, by including cases where courts have entered default judgments, Professor Clermont and Professor Eisenberg exaggerate the effect, if any, that the choice of forum has on the outcome of a case. Second, Professor Clermont and Professor Eisenberg do not demonstrate that transfers lead to more accurate outcomes. Instead, their data only supports the conclusion that a defendant's chance of winning a case improves if the defendant has selected the forum through a transfer motion. Third, Professor Clermont and Professor Eisenberg understate the costs of transfer under the open-ended standard currently employed in section 1404(a) litigation. Fourth, if Professor Clermont and Professor Eisenberg are correct that forum shopping is both pervasive and effects outcomes, Congress or the courts should address this problem directly by limiting the geographic choices available to a plaintiff who files a federal court suit. Such an approach would address any inequities resulting from forum shopping far more universally and efficiently than the case-by-case transfers currently employed under section 1404(a).
Keywords: Forum shopping